Cluster-spin-glass behavior in new ternary RE2PtGe3 compounds (RE = Tb, Dy, Ho) - L S Litzbarski; M J Winiarski; I Oshchapovsky; P Skokowski; K Synoradzki; T Klimczuk; B Andrzejewski (Materials Research Express)
Two new ternary germanides Tb _2 Pt _1.2 Ge _2.8 , Dy _2 Pt _1.15 Ge _2.85 and one already known germanium Ho _2 Pt _1.1 Ge _2.9. were synthesized using an arc melting technique. The obtained samples were investigated by powder x-ray diffraction, which indicated that all of them crystallized in a hexagonal structure with P 6/ mmm (no. 191) space group. This structure is a disordered variant of the AlB _2 aristotype that favors the formation of a spin-glass-like state. The physical properties were examined by measuring magnetic susceptibility, heat capacity and electrical resistance. Experiments indicated that all of the compounds can be classified as cluster-spin-glasses with the freezing temperature of T _f = 12.0 K, T _f = 6.0 K and T _f = 2.9 K for Tb _2 Pt _1.2 Ge _2.8 , Dy _2 Pt _1.15 Ge _2.85 and Ho _2 Pt _1.1 Ge _2.9 respectively.